COLORS IN PROPER NOUN IN UZBEK TURKISH (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2025)
Colors hold an important place in Turkish mythology, literature, and folklore. This is also reflected in names. The use of colors in proper noun creates interesting linguistic structures that have emerged under the influence of language and culture. Such proper noun are usually chosen in connection with the perceptions that colors found in nature leave on people. Throughout history, people have attributed different meanings to colors and, based on these meanings, have used names derived from colors as proper noun. Colors have been used as names for people as elements symbolizing personality, emotion, cultural values, and sometimes historical figures. Colors, which have an important place in the Turkish naming tradition, have been part of the culture and belief system. These names, which are usually shaped in an emotional, psychological, and cultural context, also have an important place in the naming tradition of the Uzbek Turks. The reflection of colors, which are part of the culture of the Uzbek Turks, in proper noun is a reflection of the traditional structure. This article will discuss proper noun created with color names identified in Uzbek Turkish. In order not to exceed the scope of the study, only information about proper noun created with the colors white, black, blue and yellow will be provided.